Learning and Coordination : Inductive Deliberation, Equilibrium and Convention. - Vanderschraaf, Peter (Studies in ethics., 2014)
Vanderschraaf develops a new theory of game theory equilibrium selection in this book. The new theory defends general correlated equilibrium concepts and suggests a new analysis of convention.